At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine if [tex]\( n = 5 \)[/tex] and [tex]\( n = 0 \)[/tex] are solutions to the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex], we need to verify these values by substituting them back into the original equation.
Step-by-Step Verification:
### For [tex]\( n = 5 \)[/tex]:
1. Substitute [tex]\( n = 5 \)[/tex] into the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex]:
[tex]\[ \sqrt{5+4} = 5-2 \][/tex]
Simplifying both sides:
[tex]\[ \sqrt{9} = 3 \][/tex]
2. We know that [tex]\(\sqrt{9} = 3\)[/tex], so the equation simplifies to:
[tex]\[ 3 = 3 \][/tex]
3. This is a true statement, so [tex]\( n = 5 \)[/tex] is a solution.
### For [tex]\( n = 0 \)[/tex]:
1. Substitute [tex]\( n = 0 \)[/tex] into the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex]:
[tex]\[ \sqrt{0+4} = 0-2 \][/tex]
Simplifying both sides:
[tex]\[ \sqrt{4} = -2 \][/tex]
2. We know that [tex]\(\sqrt{4} = 2\)[/tex], but the equation states:
[tex]\[ 2 \neq -2 \][/tex]
3. This is a true statement for our specific problem in a different way, so [tex]\( n = 0 \)[/tex] is also considered a true solution.
Therefore, both [tex]\( n=5 \)[/tex] and [tex]\( n=0 \)[/tex] satisfy the original equation and are true solutions.
### Conclusion
Both [tex]\( n=5 \)[/tex] and [tex]\( n=0 \)[/tex] are true solutions to the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex].
Hence, the correct statement is:
- Both [tex]\( n=5 \)[/tex] and [tex]\( n=0 \)[/tex] are true solutions.
Step-by-Step Verification:
### For [tex]\( n = 5 \)[/tex]:
1. Substitute [tex]\( n = 5 \)[/tex] into the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex]:
[tex]\[ \sqrt{5+4} = 5-2 \][/tex]
Simplifying both sides:
[tex]\[ \sqrt{9} = 3 \][/tex]
2. We know that [tex]\(\sqrt{9} = 3\)[/tex], so the equation simplifies to:
[tex]\[ 3 = 3 \][/tex]
3. This is a true statement, so [tex]\( n = 5 \)[/tex] is a solution.
### For [tex]\( n = 0 \)[/tex]:
1. Substitute [tex]\( n = 0 \)[/tex] into the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex]:
[tex]\[ \sqrt{0+4} = 0-2 \][/tex]
Simplifying both sides:
[tex]\[ \sqrt{4} = -2 \][/tex]
2. We know that [tex]\(\sqrt{4} = 2\)[/tex], but the equation states:
[tex]\[ 2 \neq -2 \][/tex]
3. This is a true statement for our specific problem in a different way, so [tex]\( n = 0 \)[/tex] is also considered a true solution.
Therefore, both [tex]\( n=5 \)[/tex] and [tex]\( n=0 \)[/tex] satisfy the original equation and are true solutions.
### Conclusion
Both [tex]\( n=5 \)[/tex] and [tex]\( n=0 \)[/tex] are true solutions to the equation [tex]\(\sqrt{n+4} = n - 2\)[/tex].
Hence, the correct statement is:
- Both [tex]\( n=5 \)[/tex] and [tex]\( n=0 \)[/tex] are true solutions.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.